2010
DOI: 10.1158/0008-5472.can-09-4701
|View full text |Cite
|
Sign up to set email alerts
|

CDX2 Regulates Multidrug Resistance 1 Gene Expression in Malignant Intestinal Epithelium

Abstract: The caudal-related homeobox transcription factor CDX2 has a key role in intestinal development and differentiation. CDX2 heterozygous mutant mice develop colonic polyps, and loss of CDX2 expression is seen in a subset of colon carcinoma in man. Ectopic CDX2 expression in the stomach of transgenic mice promotes intestinal metaplasia, and CDX2 expression is frequently detected in intestinal metaplasia in the stomach and esophagus. We sought to define CDX2-regulated genes to enhance knowledge of CDX2 function. HT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 44 publications
(66 reference statements)
1
38
0
Order By: Relevance
“…The multidrug resistance genes MDR1 (also called ABCB1 ) and CFTR (also called ABCC7 ), coding for two ATP‐dependent drug efflux pumps, are transcriptional downstream targets of CDX2 (Kerschner and Harris, 2012; Koh et al ., 2016; Takakura et al ., 2010; Yan et al ., 2015). We found that both MDR1/ABCB1 and CFTR/ABCC7 were significantly downregulated in CDX2‐negative patient tumors and cell lines, independent of MSI status (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The multidrug resistance genes MDR1 (also called ABCB1 ) and CFTR (also called ABCC7 ), coding for two ATP‐dependent drug efflux pumps, are transcriptional downstream targets of CDX2 (Kerschner and Harris, 2012; Koh et al ., 2016; Takakura et al ., 2010; Yan et al ., 2015). We found that both MDR1/ABCB1 and CFTR/ABCC7 were significantly downregulated in CDX2‐negative patient tumors and cell lines, independent of MSI status (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One explanation is that transfected exogenous genes may compete with the endogenous genes for binding sites on transcription factors or transcriptional coactivator and corepressor complexes. Recent studies have shown that transcription factors, Sp1 binding sites play a decisive role in the basal expression of MDR1 (human), MRP2 (rat), BCRP (human) and PepT1 (human) (Cornwell and Smith, 1993; Shimakura et al, 2006; Takakura et al, 2010; Zhang et al, 2012; Kauffmann et al, 2001). Competition with highly expressed exogenous genes might trigger the down-regulation of endogenous gene expression in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the consequences of aberrant CDX2 expression in hematopoietic cells (12). Whereas the global gene expression patterns regulated by CDX2 have been determined in embryonic stem cells, intestinal cells, and human CRC cells (9,19,21,52,53), previous studies of murine and human AML were limited to selected HOX genes that are known transcriptional targets of CDX2 during development (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%